THE EFFECT OF NUTRITIONAL INTERVENTIONS ON THE SUCCESS TREATMENT OF TUBERCULOSIS IN CHILDREN: LITERATURE REVIEW - Ardhani, Putri; Oktamianti, Puput; Manurung, Novie Irawaty Laura (Universitas Pahlawan, 2023)
ABSTRACT The incidence of tuberculosis in children is increasing and becomes a serious health problem because it can cause long-term effects such as death. TB can cause nutrient deficiencies and metabolic changes that delay recovery by suppressing immune function. Nutritional support is known to promote recovery in subjects treated for TB. The purpose of this study was to determine the effect of nutritional interventions on the success of childhood tuberculosis treatment. Literature review with 3 databases as literature search that are Pubmed, Proquest, Ebsco with analysis conducted using PRISMA. Five research articles were obtained from 3 databases relevant to the topic. Tuberculosis infection causes anorexia, malabsorption of nutrients and metabolic disorders, also causing malnutrition characterized by a decrease in fat and muscle mass. Malnutrition can be addressed with nutritional interventions that can be provided in the form of macronutient (high-protein diet) and micronutrients (vitamins and minerals). The combination of macronutrients and micronutrients can increase BMI, albumin levels, and improve fever and cough resolution. This can increase the ability of the child's immune response so that it can accelerate the recovery of children with TB. Improvement of nutrition in children is also supported by nutritional counseling that given to parents. Macronutrients and micronutrients are one of the factors supporting the success of TB treatment in children. Research on nutrition interventions is not enough, so it needs to be supported by further research on this topic so that it can provide better TB treatment results. ABSTRAK Angka kejadian tuberkulosis pada anak semakin meningkat dan menjadi masalah kesehatan yang serius karena dapat menimbulkan dampak jangka panjang seperti kematian. Tuberkulosis dapat menyebabkan defisiensi nutrisi dan perubahan metabolisme yang menunda pemulihan dengan menekan fungsi kekebalan tubuh. Dukungan nutrisi diketahui mampu mendorong pemulihan pada subjek yang mendapatkan pengobatan TB. Tujuan penelitian ini adalah untuk mengetahui pengaruh intervensi gizi terhadap keberhasilan pengobatan tuberkulosis anak. Kajian literatur dengan 3 database sebagai pencarian literatur yaitu Pubmed, Proquest, Ebsco dengan analisis dilakukan menggunakan PRISMA. Lima artikel penelitian diperoleh dari 3 database yang relevan dengan topik. Infeksi tuberkulosis menyebabkan anoreksia, malabsorbsi nutrisi dan gangguan metabolisme, juga menyebabkan malnutrisi yang ditandai dengan penurunan massa lemak dan otot. Gizi buruk dapat diatasi dengan intervensi gizi yang dapat diberikan dalam bentuk makronutrien (diet tinggi protein) dan mikronutrien (vitamin dan mineral). Kombinasi makronutrien dan mikronutrien dapat meningkatkan BMI, kadar hemoglobin, dan memperbaiki resolusi demam dan batuk. Hal ini dapat meningkatkan kemampuan respon imun anak sehingga dapat mempercepat pemulihan anak penderita TBC. Perbaikan gizi pada anak juga didukung dengan penyuluhan gizi yang diberikan kepada orang tua. Makronutrien dan Mikronutrien merupakan salah satu faktor pendukung keberhasilan pengobatan tuberkulosis pada anak-anak. Penelitian terkait intervensi gizi belum cukup banyak, sehingga perlu didukung dengan penelitian lebih lanjut, sehingga dapat memberikan hasil pengobatan TB yang lebih baik.